(3GdOQ GdefKhQ ef GdNHQ GdeCKhQ hZjQ GdeCKhQs - (3Ydj Hf eMeO Hf GdMSf Hf GdTgjO GdKGfj GdYGedj,J (B1064 (3g` s
(3ChdgG (B:s
(3hHYO ajbhd Cbd GdYHGO Ydi Hf eMeO Hf GdMSf Hf Rjf GdOjf Cfg cGf jSCdfi HYV GdENhGf ai GdOjf Yf Md CMGOjK hQOJ Yf GdCFeI GdgGOjjf s
(3BNQgG (B:s
(3abGd dg Ef di Cgd HjJ jbhdhf fSJWjY Cf fYed cPG hcPG hfSJWjY Cf dG fYed bGd s
(3GdfSNI HgG MhGTs
(3fSNI Chdis
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B450s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdMOjK h GdeUWdMs